2014 9th IEEE Conference on Industrial Electronics and Applications 2014
DOI: 10.1109/iciea.2014.6931125
|View full text |Cite
|
Sign up to set email alerts
|

Finite time stability of continuous time delay systems: Jensen's inequality-based approach

Abstract: In this study, finite-time stability of the linear continuous time-delay systems was investigated. A novel formulation of the Lyapunov-like function was used to develop a new sufficient delay-dependent condition for finite-time stability. The proposed function does not need to be positive-definite in the whole state space, and it does not need to have negative derivatives along the system trajectories. The proposed method was compared with the previously developed and reported methodologies. It was concluded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The derived result is based on algebraic inequalities only, which can be solved without using appropriate optimization methods. It has been shown that, under some circumstances, the conditions derived in this study leads to significant improvement in the finite time stability analysis, particularly in comparison with results given in [23], [24] 6. ACKNOWLEDGMENT This work has been supported by the Ministary of Science and Technological Department of Serbia under the Project ON 174 001.…”
Section: Resultsmentioning
confidence: 71%
“…The derived result is based on algebraic inequalities only, which can be solved without using appropriate optimization methods. It has been shown that, under some circumstances, the conditions derived in this study leads to significant improvement in the finite time stability analysis, particularly in comparison with results given in [23], [24] 6. ACKNOWLEDGMENT This work has been supported by the Ministary of Science and Technological Department of Serbia under the Project ON 174 001.…”
Section: Resultsmentioning
confidence: 71%
“…Theorem 15 (see [40]). System (28) associated with initial condition ( 29) is finite-time stable with respect to (α, β, h) if there exists a positive real number c such that the following conditions are satisfied:…”
Section: Miscellaneousmentioning
confidence: 99%
“…So, various stability problems for delayed systems have attracted much attention to lots of researchers. Among them, finitetime stability analysis has been of particular interest bringing forth many papers such as [40][41][42].…”
Section: Miscellaneousmentioning
confidence: 99%